A review on the relationship between maternal exposure to ambient air particulate matter (PM10) and infants’ birth weight in Asia - Ida Dalina Noordin,; Idayu Badilla Idris,; Rozita Hod,; Mohd Famey Yusoff,; Hanizah Mohd Yusoff,; Azmawati Mohamed Nawi,; Azimatun Noor Aizuddin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Introduction In 2015, almost half of low birth weight babies in the world were born in Southern Asia. It is contributed by multiple factors including maternal exposure to the elements in the environment during the antenatal period. Particulate matter (PM10) pollution in Southeast Asian region have been extensively studied with known attributions and sources. It is also known that PM10 is able to restrict foetal growth at molecular level. This review intends to investigate if the unborn in Asia are affected by air pollutants indirectly through their mothers. Methods Publications from Scopus and Science Direct digital databases in Asian region from 2015 onwards were reviewed. Details collected were the year of publication and study location, the study design, investigated air pollutants, exposure estimation methods used, the timing of exposure in relation to pregnancy, pregnancy outcome measured and the relative risk or odds of effect. Results A total of eight full text articles were included. Most of the studies were of cohort and quasi experimental designs, involving local air monitoring measurements to assign exposure. Conclusions There were more studies considered multiple air pollutants as contributing risk rather than a single pollutant. The exposure was measured according to stages of pregnancy and the trimester stratification is the most often method used. Modalities used in representing birth outcomes were not confined to birth weight alone but also included the length of gestation. Exposure to PM10 have been found to be associated with reduction in birth weight and increased risk for preterm birth in Asia.